1991
DOI: 10.1128/aac.35.9.1729
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis of the effects of different foods on absorption of cefaclor

Abstract: Cefaclor is an oral cephalosporin antibiotic which has a broad antibacterial spectrum. The purpose of this study was to investigate the effect of food on the absorption of cefaclor and to analyze kinetically the absorption process of this drug. Cefaclor was given to eight volunteers at five test times: after overnight fasting, after two rice meals (350 and 700 cal [1 cal = 4.184 JI), and after two bread meals (500 and 1,000 cal). Urinary recoveries of cefaclor and concentrations of the drug in plasma were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
3
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 8 publications
3
15
3
1
Order By: Relevance
“…All diets studied showed an insignificant decrease in the AUC O _ t except high fat non-vegetarian diet as compared to fasting state. There, however, was no significantdecrease in AUC o _ oo in all treatments, which is in agreement with published reports in the literature (6,11). Only high fat non-vegetarian diet significantly decreased the extent of absorption.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…All diets studied showed an insignificant decrease in the AUC O _ t except high fat non-vegetarian diet as compared to fasting state. There, however, was no significantdecrease in AUC o _ oo in all treatments, which is in agreement with published reports in the literature (6,11). Only high fat non-vegetarian diet significantly decreased the extent of absorption.…”
Section: Discussionsupporting
confidence: 83%
“…is hindered by food intake (7,8) or cases in whichabsorption is accelerated by food intake (9,10) The bioavailability of cefaclor has been reported to be reduced by food intake (11). However, in a recent study with the modified release formulation of cefaclor the bioavailability of cefaclor was found to be increased with the co-administration of cefaclor with food (12).There is a wide variation in dietary practices and beliefs among populations throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…There was a 50% increase in C max when rice diet was compared with fasting (P<O.OOI) this was followed by 33% increase with low-fat vegetarian diet (wheat based) (P<O.OOI) and 29% with high-fat non-vegetarian diet (P<O.OI).The increase in C max by rice diet, followed by low-fat non-vegetarian diet is in agreement with reported food effect by Oguma et al (19). Oguma et al have reported that rice diet decreased the rate of absorption more than the bread diet with cefador immediate release formulation.…”
Section: Discussionsupporting
confidence: 81%
“…This is in agreement with the results reported by other workers. (9,19).The increase was inversely related to the fat content of the diet. Both high-fat vegetarian and non-vegetarian diets produced a smaller increase in tmax (37.5%) as compared to the respective low-fat vegetarian and nonvegetarian diets (100%).…”
Section: Discussionmentioning
confidence: 72%
“…Food preferences contribute to the physiological diversity among individuals, especially in patients, because food may influence metabolic patterns and the efficacy of drugs [12,13] . It is well known that a high-fat diet (HFD) is a major contributing factor in the prevalence of NAFLD, which is defined as the significant accumulation of fat in the liver (>5%-10% of the weight of the liver), which can be as high as 76% in obese subjects [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%